Continuing education for the public secondary school library personnel in the Division of Quezon City needs assessment - Bautista, Elizabeth S.; Faderon, Rosalie B.; Picache, Ursula G. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1984)
The study assessed the continuing education needs of the secondary school library personnel in the Division of City School, Quezon City. Specifically, it aimed to identify the library personnel's actual job activities, their perceived continuing education needs and preferred continuing education modes and course content.
The library personnel were surveyed through the universal poll method, a total enumeration of the entire population. The study used the descriptive survey method and utilized theses research instruments: survey questionnaire were personnally handed to forty-one respondents out of forty-six secondary school library personnel. Five did not wish to be included in the survey for various reasons. All forty-one questionnaires were returned with 100 percent usable data.
The major findings of this study are: 1) Three or almost 9 percent of the thirty four secondary schools in the Division have no library personnel. 2) All except one of the respondents are females and more than three-fourths of them are more than 30 years old. 3) Thirty-three respondents are holders of the Bachelor of Science in Education degree with Library Science as their major specialization. 4) More than half of the respondents have pursued graduate courses in library science and in other subject areas. 5) Six of the library personnel are members of library associations. 6) Majority of the respondents carry the official designation of Secondary School Teacher (Library Science); since most of them have the necessary educational qualifications, they were assigned to the library. 7) Of the thirty-two who have attended in other subject areas while only ten have attended continuing education programs in the field of library science. Professional growth was their most important reason for attending continuing education programs. The most common mode employed in these continuing education programs that they attended was "Seminar-workshops". 8) The primary reason of nine respondents for not attending continuing education programs was that there was "no funding received". 9) The Division has not been providing continuing education programs to the library personnel. Majority of the respondents chose the Institute of Library Science of the University of the Philippines as the institution to conduct continuing education programs for them, for its "teaching competence and expertise". 10) The library activities performed by these public secondary school library personnel are the very elementary ones which do not need special technical training. These could be attributed to the lack of specially trained library personnel. 11) The school library personnel's perceived needs as regards continuing education course content are: Modern trends in librarianship (covering all areas/aspects of the subject field); cataloging and classification; administration of school libraries; reference services; selection and acquisition; and public relations. They perceived these three continuing education modes as the most effective: Seminars and Interlibrary visitations; Workshops; and Guided educational tours.
These are some of the recommendations put forth: 1) Library associations like the Philippine Association of School Librarians (PASL) and other agencies like the Division of City Schools of Quezon City, if they would be involved in providing continuing education for the school library personnel, should see to it that each program offered will be great help to these personnel. A continuing education program model that would meet the individual needs of these library personnel and which are job-related must be worked out. Topics to be discussed must be those perceived by them. 2) Continuity of program offerings must be organized in a sequential manner and continuously. 3) Planners of continuing education programs should strive to have a homogenous group with a limited number of participants to allow for more detailed discussions of any topic as well as more interaction among the participants. 4) An evaluation of these continuing education programs must be made to find out weak points so that appropriate strengthening of the programs would be made. Suggestions and recommendations from participants should be studied and discussed by the planners and these should be integrated into the forthcoming programs. 5) The Division should draw up a plan for the library personnel who are interested in formal or informal continuing education programs. They should be given equal opportunities to grow profesionally on a rotation basis. Funds must be provided to enable them to attend continuing education programs. 6) The library personnel should strive to acquire new knowledge and/or update or upgrade knowledge, skills and competencies in the field through continuing education programs; if the Division fails to sponsor them, the personnel should find ways and means to attend continuing education programs conducted by other concerned groups.
Mimeographed.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Library education (Continuing education)--Philippines--Quezon City; Library employees--Philippines--Quezon City